Haunts and specters in Chimamanda Ngozi Adichie’s Biafran (Re)visitations - Anita Harris Satkunananthan (Penerbit Universiti Kebangsaan Malaysia, 2018)
Chimamanda Ngozi Adichie writes about the Nigeria-Biafra war and its effect on the Igbo in more than one novel in her oeuvre, which is written entirely in English as a cosmopolitan Nigerian diasporic author currently residing in the United States of America. In Half of a Yellow Sun, Adichie memorializes the intellectual and artistic culture of Nsukka before and during the Nigeria-Biafra war. This article postulates that the seed for this bestselling novel is also evident in the play For Love of Biafra, penned by Adichie in her teens. This English-language play focuses directly on the effects of the Nigeria-Biafra war upon the personal life of the protagonist, Adaobi. I examine the manner in which the play demonstrates the function of memory upon second-generation descendants of the Nigeria-Biafra War survivors by examining the impact of postmemory through the lens of Derridean hauntology which I have expanded as a postcolonial feminine hauntology, examining the manner in which the specters of Biafra are conjured in Adichie’s Biafran texts. I connect this to the ways in which Adichie’s narration of the Nigeria-Biafra war evolves in Half of a Yellow Sun to problematize the question of who may witness, bear testimony and author narrative. The article’s findings tie the act of narration to empowerment, identification, the experience of trauma to unearth the myriad ways in which the specter of the Nigeria-Biafra war is recreated in fictions by second-generation diasporic and cosmopolitan authors such as Adichie.